IL‐33 signalling contributes to pollutant‐induced allergic airway inflammation. Issue 12 (19th September 2018) - De Grove, Katrien C.; Provoost, Sharen; Braun, Harald; Blomme, Evy E.; Teufelberger, Andrea R.; Krysko, Olga; Beyaert, Rudi; Brusselle, Guy G.; Joos, Guy F.; Maes, Tania
Summary: Background: Clinical and experimental studies have identified a crucial role for IL‐33 and its receptor ST2 in allergic asthma. Inhalation of traffic‐related pollutants, such as diesel exhaust particles (DEP), facilitates the development of asthma and can cause exacerbations of asthma. However, it is unknown whether IL‐33/ST2 signalling contributes to the enhancing effects of air pollutants on allergic airway responses. Objective: We aim to investigate the functional role of IL‐33/ST2 signalling in DEP‐enhanced allergic airway responses, using an established murine model. Methods: C57BL/6J mice were exposed to saline, DEP alone, house dust mite (HDM) alone or combined DEP+HDM. To inhibit IL‐33 signalling, recombinant soluble ST2 (r‐sST2) was given prophylactically (ie, during the whole experimental protocol) or therapeutically (ie, at the end of the experimental protocol). Airway hyperresponsiveness and the airway inflammatory responses were assessed in bronchoalveolar lavage fluid (BALF) and lung. Results: Combined exposure to DEP+HDM increased IL‐33 and ST2 expression in lung, elevated inflammatory responses and bronchial hyperresponsiveness compared to saline, sole DEP or sole HDM exposure. Prophylactic interference with the IL‐33/ST2 signalling pathway impaired the DEP‐enhanced allergic airway inflammation in the BALF, whereas effects on lung inflammation and airway hyperresponsiveness were minimal. Treatment with r‐sST2 at the end of the experimental protocol did not modulate the DEP‐enhanced allergic airway responses. Conclusion: Our data suggest that the IL‐33/ST2 pathway contributes to the onset of DEP‐enhanced allergic airway inflammation.